Antipsychotic drug use and associations with neuropsychiatric symptoms in persons with impaired cognition: a cross-sectional study. (16th November 2016) - Kuronen, Marja; Kautiainen, Hannu; Karppi, Pertti; Hartikainen, Sirpa; Koponen, Hannu
Abstract: Background: Neuropsychiatric symptoms (NPS) in cognitive disorders impair quality of life, increase caregiver stress, and may lead to earlier institutionalization and death. The objective of this study was to investigate the use of antipsychotics among persons with cognitive impairment in home care and residential care, and its associations with NPS and personal characteristics. Methods: Data were collected in the South Savo Hospital District area with 105 000 inhabitants, where 66 of 68 institutions providing long-term residential care and 20 of 21 municipal home care producers joined the study. Nurses recorded the current use of drugs, the activities of daily living (ADL), prevalence of diagnosed dementia, and assessed the cognitive status and the prevalence of recent NPS based on the item list of the Neuropsychiatric Inventory (NPI). Results: The study population was 1909 persons with cognitive impairment, and 1188 of them lived in residential care. Antipsychotics were used by 563 (29.5%) persons in the whole study population. In residential care 448 (37.7%) used antipsychotics and the corresponding figure in home care was 115 (15.9%). In the multivariate analysis, the antipsychotic use was associated with living in residential care, benzodiazepine use, and with NPS symptoms agitation/aggression (OR =1.70, 95% CI =1.16–2.48), disinhibition (OR =2.33, 95% CI =1.31–4.15), hallucinations (OR =2.77, 95% CI =1.69–4.55), and delusions (OR =1.71, 95% CI =1.01–2.91). Conclusions: Antipsychotic use was common among persons with cognitive impairment. The results suggest that antipsychotics are commonly used to treat hyperactivity and psychotic symptoms, especially in residential care.